Industrial training report: Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) / Nurul Natasya Muhammad Firdaus Ambrose - Muhammad Firdaus Ambrose, Nurul Natasya (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This report is a summary of my industrial training experience at Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) from August 5th to January 17th, 2025. It is part of the Bachelor of Information Science (Hons.) Library Management degree, which aims to provide students with practical experience in the professional workplace. The report is divided into four chapters, each detailing the organization's structure, functions, and activities. Chapter 1 introduces the report and provides background information about PERPUSTAM, including its location, logo, vision, mission, objectives, operating hours, rules, facilities, services, and organizational structure. Chapter 2 focuses on the organization's internal structure and functions, highlighting the roles of various departments. Chapter 3 details the activities and responsibilities undertaken during the internship, including tasks like cataloging, shelving, weeding, organizing events, digitization, filing, and internal audits. Chapter 4 concludes by reflecting on the application of knowledge, personal growth, and key lessons learned during the internship, addressing limitations, and providing recommendations for future improvements.